Application of shear wave elastography in the assessment of renal cortical elasticity in patients with hypertension - Dai, Miaolei; Wang, Liang; Luo, Jianfeng (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the clinical utility of shear wave elastography (SWE) for measuring renal cortical elasticity in patients with hypertension.MethodsFollowing the diagnostic criteria established in the 2020 International Society of Hypertension Global Hypertension Practice Guidelines, 44 patients with essential hypertension from our hospital’s Department of Cardiology were enrolled alongside 46 healthy controls during the same period. General demographic data and blood biochemical indicators of renal function were documented for all participants. All subjects underwent two-dimensional ultrasound and SWE examinations to obtain conventional ultrasound parameters and Young’s modulus (YM) values of the right renal cortex. Parameters were compared between the two groups. Multiple linear regression analysis was conducted to identify relationships between the YM value of the right renal cortex and general demographic data, conventional ultrasound indicators, and renal function parameters in the hypertensive group.ResultsDisease duration, systolic blood pressure, and diastolic blood pressure in the hypertensive group were significantly higher than those in the control group (p < 0.05). The YM value of the right renal cortex in the hypertensive group was significantly higher than that in the control group (p < 0.05). Correlation analysis revealed a strong positive correlation between the YM value of the right renal cortex and the duration of hypertension (r = 0.747, p < 0.001). No significant correlations were found between right renal cortex YM and age, blood pressure, right renal volume, right renal cortex thickness, peak systolic velocity, resistive index of the right renal artery trunk, blood urea nitrogen, blood creatinine, or uric acid (p > 0.05). Multivariate linear regression analysis identified duration of hypertension as an independent predictor of right renal cortex YM. The regression equation was determined to be Y = 8.63 + 0.41 X1.ConclusionSWE may serve as a valuable non-invasive screening tool for early detection of hypertension-related renal changes before conventional parameters show abnormalities. The positive correlation between cortical stiffness and hypertension duration suggests SWE could assist clinicians in risk stratification and monitoring progression of subclinical renal damage, potentially enabling earlier therapeutic interventions to prevent progression to chronic kidney disease.